Śrī Puṣpamālā prakaraṇa : mūḷagāthā, anuvāda, kathā, akārādikrama sahita - Hemacandra Sūri, active 12th century; Śāha, Kāntibhāī Bī.; Pradyumnācārya; Hemacandra Sūri, active 12th century; Hemacandra Sūri, active 12th century (Amadāvāda : Śrī Śrutajñāna Prasāraka Sabhā, 2003)
Verse work on Jaina doctrines with Gujarati translation.
Includes index.
Mode of access: Internet.
Gujarati and Prakrit.
Keywords: Jainism -- Doctrines -- Early works to 1800.